2023
DOI: 10.3390/w15050892
|View full text |Cite
|
Sign up to set email alerts
|

An Innovative Sorption Technology for Removing Microplastics from Wastewater

Abstract: This study is focused on technology development for microplastic removal from wastewater using a sorption process, which would be suitable not only as a tertiary stage of purification in wastewater treatment plants but also for other waters, e.g., process water and surface water. Therefore, cheap natural materials such as zeolites and bentonites were tested as possible sorbents. This study aims not only at sorbent selection but also at their possible modification by a special water regime improving sorption ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Nonetheless, zeolites and coals, including those indigenous to Kazakhstan, demonstrate notable sorption capabilities against organic contaminants, heavy metals, and radionuclides [43][44][45][46]. Published findings suggest that sand filters could be replaced effectively by aluminosilicate filter media [47], and zeolites have shown promise in microplastic treatment in wastewater [48], while granular coals, when combined with ion exchange and microfiltration, have demonstrated efficacy in removing certain microplastic types [49]. However, research on microplastic water treatment primarily focuses on wastewater and is limited to specific types and sizes of microplastics.…”
Section: Methods Of Sampling and Analyzing Tap Watermentioning
confidence: 99%
“…Nonetheless, zeolites and coals, including those indigenous to Kazakhstan, demonstrate notable sorption capabilities against organic contaminants, heavy metals, and radionuclides [43][44][45][46]. Published findings suggest that sand filters could be replaced effectively by aluminosilicate filter media [47], and zeolites have shown promise in microplastic treatment in wastewater [48], while granular coals, when combined with ion exchange and microfiltration, have demonstrated efficacy in removing certain microplastic types [49]. However, research on microplastic water treatment primarily focuses on wastewater and is limited to specific types and sizes of microplastics.…”
Section: Methods Of Sampling and Analyzing Tap Watermentioning
confidence: 99%
“…Recent studies have reported on the efficiency of native and/or modified bio-substrates as adsorbents for the removal of micro-and nanoparticles from drinking water and/or wastewaters, which include bio-nano adsorbents (e.g., lignin-zeolite composite nanofiber) [58], natural adsorbents such as zeolites and bentonites [63], biodegradable superhydrophobic sponges [64], and superhydrophobic cotton fabrics via chemical modification that display removal efficiencies of microplastic particles higher than 99% from water bodies [33]. Similarly, the surface modification of waste biomass, including coconut, sugarcane, and banana peel bagasse, has been evaluated using a non-ionic surfactant to increase the adsorption capacity toward microplastic particles from wastewater.…”
Section: Introductionmentioning
confidence: 99%
“…The densities of microplastics vary depending on the type of particle, influencing their dispersion in aquatic environments. Low-density microplastics are found on water surfaces and in neustonic environments, while high-density microplastics settle in deeper waters and benthic zones [19][20][21].…”
Section: Introductionmentioning
confidence: 99%